Conduction of reparative dentin: A pulp protecting approach by indirect pulp capping in deep carious lesion with biodentine (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
This case report represents, the treatment of deep carious lesion in a male was done by using indirect pulp capping with biodentine. The clinical and radiological outcomes were evaluated. The patient was presented with mild to moderate sensitivity on thermal (cold) stimulation and discomfort associated with eating in the left mandibular first molar. The clinicoradiographical examination revealed a distoocclusal carious lesion, very close to the pulp, absence of radiolucencies in the periapical region and no periodontal space widening. Pulp sensitivity was confirmed by thermal pulp vitality test. Indirect pulp capping treatment was performed with biodentine. Following 6 months of the treatment, the clinical symptoms were resolved and a calcific bridge was found at the dentin over the pulp and biodentine interface that was indicative the evidence of reparative dentin formation.